Evaluation of the nasolabial angle of the Komarapalayam population - Kohila Kandhasamy; Neetika Mukhija Prabu; Sivaraj Sivanmalai; Pannaikadu Somasundaram Prabu; Abraham Philip; Jwala C Chiramel (Wolters Kluwer Medknow Publications, 2012)
Esthetic features are different from one race to another, and this should be considered during the treatment planning. The great variance in soft tissue drape of the human face complicates accurate assessment. The nose-lip-chin relationships are exceedingly important in determining the facial esthetics. One important soft tissue parameter in orthodontic diagnosis is the nasolabial angle. The purpose of this study was to establish norms for nasolabial angle as proposed by Fitzgerald for the Komarapalayam population. Normative data for the three nasolabial parameters were produced from a sample of 40 (20 male and 20 female) adults determined by the authors to have well-balanced faces. Mean and standard deviation values from this pooled sample demonstrated a lower border of the nose to Frankfort horizontal plane angle of 18° ± 7°, upper lip to Frankfort horizontal plane angle of 98° ± 5°, and nasolabial angle of 116° ± 10°. No statistically significant difference was demonstrated between the values for men and women in this study, but men did have a slightly larger nasolabial angle.